1996
DOI: 10.1007/bf01209120
|View full text |Cite
|
Sign up to set email alerts
|

In vitro analysis of cancer prevention by a mycobacterial antigen complex and of cancer-promoted inhibition of immune reactions

Abstract: The antigen complex A60 of Mycobacterium bovis bacillus Calmette-Guérin protected mice against experimental tuberculous infection, and prevented cancer development after challenge with EMT 6 cells. Although humoral and cellular immune reactions elicited by A60 in vivo remained unaffected in cases of tumor rejection, they were suppressed in the case of neoplastic growth. In the present work, these in vivo observations were analyzed by in vitro techniques. Activated macrophages played a major role, and cytolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1996
1996
1998
1998

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Previous studies [14] have shown that A60 successfully protects 60-70% of the mice from tumour challenge. The tumour cells are able to develop as lethal cancers in the remainder of cases, primarily by a process involving inhibition of the activation and function of both T lymphocytes and M8s [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [14] have shown that A60 successfully protects 60-70% of the mice from tumour challenge. The tumour cells are able to develop as lethal cancers in the remainder of cases, primarily by a process involving inhibition of the activation and function of both T lymphocytes and M8s [14,31].…”
Section: Discussionmentioning
confidence: 99%
“…The cytolytic ability of CTL (A) and MΦ (B) were then measured by a chromium release assay, using labelled EMT 6 cells as targets. The activating action of A60 on cytolytic cells [ 80] is evident.…”
Section: The Prophylactic Action Of Tma Complexes Against Experimentamentioning
confidence: 99%
“…On the contrary, B‐cell activation by specific T cells previously incubated with tumour cells was clearly inhibited ( Fig. 6B) [ 80]. Consequently, the tumour‐promoted alteration of the humoral immune system seems to be due to an inhibitory interaction of cancer cells with T lymphocytes ( Fig.…”
Section: The Inhibitory Effects Of Neoplasia On the Immune Systemmentioning
confidence: 99%
See 2 more Smart Citations